Luminescent material capable of emitting blue and blue light, preparation method of luminescent material and low-blue-light LED light source prepared from luminescent material

By doping Bi3+ in the garnet matrix, a blue-glazed fluorescent material was prepared and combined with a purple-glazed LED chip, the problems of low color rendering index and blue-glazed hazards were solved, and a full-spectral wLED with high color rendering index and low blue light were achieved.

CN119529836AInactive Publication Date: 2025-02-28JIANGXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411232994.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing white LEDs have low color rendering index and lack of green light, and strong blue light may be harmful to human health.

Method used

Bi3+ doped blue-glazed fluorescent material in garnet matrix is ​​used in combination with the Vane LED chip to achieve a low blue-glazed full spectrum wLED with high color rendering index, high luminous efficiency and high thermal stability.

Benefits of technology

It effectively fills the "gulge" of green light in white LEDs, has excellent color rendering performance, reduces blue light hazards, and is simple in process and low production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529836A_ABST
    Figure CN119529836A_ABST
Patent Text Reader

Abstract

The invention discloses a broadband blue-blue light luminescent material, a preparation method thereof and an LED light source containing the luminescent material. The chemical formula of the luminescent material is A3B2Ge3O12: xBi < 3 + >, wherein A is one or a combination of Ca, Sr, Ba, Zn and Mg divalent metal ions; b is one or a combination of La, Gd, Lu, Sc, Y, Al, Ga and In trivalent metal ions; bi < 3 + > is a luminescent central ion; the specific value is 0 lt; and x is less than or equal to 0.20. The powder material is prepared by adopting a high-temperature solid-phase method, and the method is simple in process, environment-friendly and low in cost. The luminescent material provided by the invention can realize simultaneous coverage of blue light and cyan light areas, reduces blue light harm, fills up the'gullies' of cyan light, improves the color rendering index of a white light source LED, reduces related color temperature, can be used as a fluorescence conversion material, and has a huge application prospect in the fields of low-blue-light full-spectrum illumination and high-power laser illumination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid-state lighting of inorganic solid luminescent materials doped with transition group ions, and in particular to a garnet-based blue-cyan fluorescent material activated by trivalent bismuth ions, a preparation method thereof, and an LED light source comprising the luminescent material. Background Art

[0002] In recent years, with the progress made in the study of the correlation between lighting sources and human health, the relationship between the wavelength of light and the human body rhythm has been revealed. For example, short-wave purple light is beneficial to the synthesis of vitamin D, and it also has a positive effect on skin and mucous membrane ulcers, acne, etc. Green light has a calming and relaxing effect on nerves. Orange light has the effect of promoting blood circulation, metabolism and thyroid function. With the development of human society, more and more people's working environment has changed from outdoor environment to indoor environment. Long-term exposure to artificial environment with uneven spectrum may be detrimental to human physiological health. Therefore, researchers have shifted their attention to the lighting quality of human life and human performance. Correspondingly, full-spectrum lighting with uniform and continuous spectrum, high color rendering index, good color reproducibility, and similar to natural light has emerged.

[0003] Full spectrum wLED usually means that the spectrum wavelength of wLED covers the wavelength range that the human eye can distinguish (400-700nm), which is an artificial natural light source. The earliest commercial wLED was made by coating yellow YAG:Ce on a blue InGaN chip. 3+ However, the prominent disadvantage of this wLED is the lack of red and cyan components, which leads to high correlated color temperature (CCT>5000K) and low color rendering index (CRI<80). In order to reduce CCT and improve CRI, people often need to add additional cyan fluorescent materials and commercial red fluorescent materials CaAlSiN3:Eu 2+ However, from the perspective of full spectrum, choosing a commercial 450nm blue LED chip will face many problems. On the one hand, it lacks the 400-450nm band required by the full spectrum; on the other hand, the strong blue light is easy to cause blue light hazards that affect human health. Although some people have recently proposed using near-ultraviolet LED chips to excite multi-color phosphors to achieve full-spectrum wLED, considering the low luminous efficiency (~44%) and strong energy of near-ultraviolet light, it is easy to accelerate the aging of the packaging resin. Obviously, it is not the most sensible excitation source for full-spectrum wLED. However, purple LED chips (λ em =395-420nm) has attracted wide attention from full-spectrum wLED researchers due to its high light conversion efficiency (~80%). However, blue light is the basic light color for realizing wLED. Therefore, the development of fluorescent materials covering blue-cyan light excited by purple LED chips is particularly important for the realization of low-blue full-spectrum LED.

[0004] Bi 3+ As a sensitizer or activator in luminescent materials, its spectral behavior has been widely studied. 3+ The absorption of Bi is mainly concentrated in the near-ultraviolet-violet region, with no reabsorption, so it is energy efficient. Benefiting from the exposed 6s and 6p orbitals, Bi 3+ It has a widely adjustable luminescence spectrum and is easily affected by different crystal field environments, thus opening up great possibilities for ion regulation. The garnet matrix, due to its good rigid structure and rich crystal sites, has achieved multi-color emission of various rare earth luminescence centers and transition group ion doping, and is a good matrix system.

[0005] To this end, the present invention uses garnet as a matrix to prepare Bi 3+ The doped blue-cyan fluorescent material, combined with the purple light chip, can realize a low-blue light full-spectrum wLED with high color rendering index, high luminous efficiency and high thermal stability. Summary of the invention

[0006] The purpose of the present invention is to provide a luminescent material emitting blue-cyan light, a preparation method and an LED light source containing the material, aiming to solve the problems of low color rendering index, lack of cyan light, and blue light hazards of existing white light LEDs.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a luminescent material that emits blue-cyan light. The chemical formula of the luminescent material is A3B2Ge3O 12 :xBi 3+ ,in:

[0009] A is one of Ca, Sr, Ba, Zn, Mg divalent metal ions or a combination thereof;

[0010] B is one of trivalent metal ions of La, Gd, Lu, Sc, Y, Al, Ga, and In, or a combination thereof.

[0011] x is Bi 3+ The doping concentration is 0 <x≤0.20。

[0012] According to an embodiment of the present invention, the luminescent material is characterized in that it can be excited by a 330-420nm near-ultraviolet light / purple light chip to emit adjustable broadband blue-cyan light, and its emission range is: 420-580nm.

[0013] According to an embodiment of the present invention, the chemical composition of the luminescent material may be: Sr2MgLaScGe3O 12 :0.10Bi3+ 、Sr2MgGdScGe3O 12 :0.10Bi 3+ 、Sr2MgYScGe3O 12 :0.10Bi 3+ 、Sr2MgLuScGe3O 12 :0.10Bi 3+ 、Sr2MgAlScGe3O 12 :0.10Bi 3+ 、Sr2MgGaScGe3O 12 :0.10Bi 3+ 、Sr2MgInScGe3O 12 :0.10Bi 3+ 、Sr2ZnLaScGe3O 12 :0.10Bi 3+ 、Sr2ZnGdScGe3O 12 :0.10Bi 3+ 、Sr2ZnYScGe3O 12 :0.10Bi 3+ 、Sr2ZnLuScGe3O 12 :0.10Bi 3+ 、Sr2ZnAlScGe3O 12 :0.10Bi 3+ 、Sr2ZnGaScGe3O 12 :0.10Bi 3+ 、Sr2ZnInScGe3O 12 :0.10Bi 3+ 、Ca2MgLaScGe3O 12 :0.10Bi 3+ 、Ca2MgGdScGe3O 12 :0.10Bi 3+ 、Ca2MgYScGe3O 12 :0.10Bi 3+ 、Ca2MgLuScGe3O 12 :0.10Bi 3+ 、Ca2MgAlScGe3O 12 :0.10Bi 3+ 、Ca2MgGaScGe3O 12 :0.10Bi 3+ 、Ca2MgInScGe3O 12 :0.10Bi 3+ 、Ca2ZnLaScGe3O 12 :0.10Bi 3+、Ca2ZnGdScGe3O 12 :0.10Bi 3+ 、Ca2ZnYScGe3O 12 :0.10Bi 3+ 、Ca2ZnLuScGe3O 12 :0.10Bi 3+ 、Ca2ZnAlScGe3O 12 :0.10Bi 3+ 、Ca2ZnGaScGe3O 12 :0.10Bi 3+ 、Ca2ZnInScGe3O 12 :0.10Bi 3+ 、Ba2MgLaScGe3O 12 :0.10Bi 3+ 、Ba2MgGdScGe3O 12 :0.10Bi 3+ 、Ba2MgYScGe3O 12 :0.10Bi 3+ 、Ba2MgLuScGe3O 12 :0.10Bi 3+ 、Ba2MgAlScGe3O 12 :0.10Bi 3+ 、Ba2MgGaScGe3O 12 :0.10Bi 3+ 、Ba2MgInScGe3O 12 :0.10Bi 3+ 、Ba2ZnLaScGe3O 12 :0.10Bi 3+ 、Ba2ZnGdScGe3O 12 :0.10Bi 3+ 、Ba2ZnYScGe3O 12 :0.10Bi 3+ 、Ba2ZnLuScGe3O 12 :0.10Bi 3+ 、Ba2ZnAlScGe3O 12 :0.10Bi 3+ 、Ba2ZnGaScGe3O 12 :0.10Bi 3+ 、Ba2ZnInScGe3O 12 :0.10Bi 3+ 。

[0014] According to the embodiment of the present invention, the luminescent material has high photoluminescence efficiency and luminescence stability, and has broadband blue-cyan light emission, and has great application potential in the fields of full-spectrum lighting and high-power laser lighting.

[0015] According to another aspect of the present application, a method for preparing a luminescent material is provided, which has the advantages of simple process and low production cost.

[0016] The present invention also provides a method for preparing the luminescent material, the method comprising the following steps:

[0017] (1) According to the chemical formula of the material A3B2Ge3O 12 :xBi 3+ Weigh the compound raw materials and additives of each element in a stoichiometric ratio, add grinding media and grind thoroughly;

[0018] (2) placing the obtained mixture into a corundum crucible, placing it in a box furnace for pre-sintering, cooling it naturally to room temperature after the pre-sintering is completed, and grinding the obtained pre-sintered product thoroughly, and then placing it in a tube furnace for calcining in an air atmosphere, and cooling it to room temperature with the furnace after the sintering is completed;

[0019] (3) The sintered product obtained above is fully ground, cleaned, dried and sieved to obtain the target material;

[0020] Optionally, the auxiliary agent described in step (1) may be selected from: NaCl, Na2O, LiCl, Li2CO3, H3BO3, Si3N4, Gd2O3, CaF2, SrF2, BaF2, MgF2, ZnF2, AlF3;

[0021] Optionally, the grinding medium in step (1) may be: methanol, ethanol, ultrapure water;

[0022] Optionally, the grinding time in step (1) can be selected as: 20-120 min;

[0023] Optionally, the pre-firing temperature in step (2) may be 100-300° C., and the holding time may be 2-4 hours.

[0024] Optionally, the calcination temperature in step (2) may be 1200-1400° C., and the holding time may be 2-24 hours.

[0025] Optionally, the cleaning reagent in step (3) can be selected from: acetic acid, ethanol, methanol, acetone, ultrapure water. The centrifugation time is: 3-5min, and the centrifugation speed is: 2000-5000 rpm;

[0026] Optionally, the standard test sieve mesh number and the corresponding aperture in step (3) may be: 30 mesh / 60 mesh / 120 mesh.

[0027] The present invention also provides an LED light source comprising the luminescent material, comprising an excitation light source and a luminescent material that can be excited by the excitation light source, wherein the luminescent material includes the blue-cyan light emitting fluorescent material described in the present invention.

[0028] According to an embodiment of the present invention, the wavelength range of the excitation light source is in the near ultraviolet light-violet light region, optionally, in the range of 330-420 nm.

[0029] According to an embodiment of the present invention, the LED light source has a full spectrum and has a high color rendering index and a low correlated color temperature.

[0030] Beneficial effects of the present invention:

[0031] In summary, compared with the prior art, the advantages of the present invention are:

[0032] (1) The luminescent material related to the present invention has both blue light and cyan light, which can effectively fill the cyan light "gap" in white light LEDs, and has high external quantum efficiency and good color rendering performance.

[0033] (2) The excitation range of the luminescent material related to the present invention is relatively wide and is located in the near-ultraviolet light-violet light region (330-420nm), which can effectively avoid the use of 450-465nm blue light chips and reduce the harm of blue light.

[0034] (3) The luminescent material manufacturing method related to the present invention is feasible, the production process is simple, and it is convenient for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the XRD spectrum of the luminescent material prepared in Example 1.

[0036] Figure 2 This is the excitation and emission spectra of the luminescent material prepared in Example 1.

[0037] Figure 3 This is the electroluminescence spectrum of the LED white light source prepared in Example 29.

[0038] Figure 4 This is the electroluminescence spectrum of the LED white light source prepared in Comparative Example 1. Specific implementation plan

[0039] Example 1

[0040] Sr2MgGdScGe3O 12 :0.10Bi 3+ And its preparation

[0041] According to the stoichiometric ratio, weigh Gd2O3: 0.3626g, SrCO3: 0.5757g, Bi2O3: 0.0466g, Sc2O3: 0.1379g, MgO: 0.0804g, GeO2: 0.6277g, a total of 1.8309g. After fully mixing the above raw materials, fully dry grind for 40-60 minutes or wet grind for 20-30 minutes. Put the above mixture into a corundum crucible and move it into an oven at 200°C. After keeping it warm for 2h, cool it to room temperature with the oven. Fully dry grind the pre-burned sample for 20min, put it into the original corundum crucible and move it into a tubular furnace. Heat it to 600°C at a heating rate of 5°C / min. After keeping it warm for 30min, continue to heat it to 1300°C, keep it warm for 8-10h, and then cool it to room temperature with the furnace. The sintered product is fully ground, cleaned, dried, and sieved to obtain a Bi 3+ Doped blue-cyan light-emitting fluorescent material.

[0042] Example 2

[0043] Sr2MgLaScGe3O 12 :0.10Bi 3+ And its preparation

[0044] According to the stoichiometric ratio, weigh La2O3: 0.3258g, SrCO3: 0.5757g, Bi2O3: 0.0466g, Sc2O3: 0.1379g, MgO: 0.0804g, GeO2: 0.6277g, a total of 1.7941g. After fully mixing the above raw materials, fully dry grind for 40-60 minutes or wet grind for 20-30 minutes. Put the above mixture into a corundum crucible and move it into an oven at 200°C. After keeping it warm for 2h, cool it to room temperature with the oven. Fully dry grind the pre-burned sample for 20min, put it into the original corundum crucible and move it into a tubular furnace. Heat it to 600°C at a heating rate of 5°C / min. After keeping it warm for 30min, continue to heat it to 1300°C, keep it warm for 8-10h, and then cool it to room temperature with the furnace. The sintered product is fully ground, cleaned, dried, and sieved to obtain a Bi 3+ Doped blue-cyan light-emitting fluorescent material.

[0045] Example 3

[0046] Sr2MgYScGe3O 12 :0.10Bi 3+ And its preparation

[0047] According to the stoichiometric ratio, weigh Y2O3: 0.2258g, SrCO3: 0.5757g, Bi2O3: 0.0466g, Sc2O3: 0.1379g, MgO: 0.0804g, GeO2: 0.6277g, a total of 1.6941g. After fully mixing the above raw materials, fully dry grind for 40-60 minutes or wet grind for 20-30 minutes. Put the above mixture into a corundum crucible and move it into an oven at 200°C. After keeping it warm for 2h, cool it to room temperature with the oven. Fully dry grind the pre-burned sample for 20min, put it into the original corundum crucible and move it into a tubular furnace. Heat it to 600°C at a heating rate of 5°C / min. After keeping it warm for 30min, continue to heat it to 1300°C, keep it warm for 8-10h, and then cool it to room temperature with the furnace. The sintered product is fully ground, cleaned, dried, and sieved to obtain a Bi 3+ Doped blue-cyan light-emitting fluorescent material.

[0048] Example 4

[0049] Sr2MgLuScGe3O 12 :0.10Bi 3+ And its preparation

[0050] According to the stoichiometric ratio, weigh Lu2O3: 0.3980g, SrCO3: 0.5757g, Bi2O3: 0.0466g, Sc2O3: 0.1379g, MgO: 0.0804g, GeO2: 0.6277g, a total of 1.8663g. After fully mixing the above raw materials, fully dry grind for 40-60 minutes or wet grind for 20-30 minutes. Put the above mixture into a corundum crucible and move it into an oven at 200°C. After keeping it warm for 2h, cool it to room temperature with the oven. Fully dry grind the pre-burned sample for 20min, put it into the original corundum crucible and move it into a tubular furnace. Heat it to 600°C at a heating rate of 5°C / min. After keeping it warm for 30min, continue to heat it to 1300°C, keep it warm for 8-10h, and then cool it to room temperature with the furnace. The sintered product is fully ground, cleaned, dried, and sieved to obtain a Bi 3+ Doped blue-cyan light-emitting fluorescent material.

[0051] Example 5-28

[0052] The above-mentioned Examples 1-4 are detailed examples, and the difference between Examples 5-28 is only in the raw materials and pre-sintering / calcining temperatures, and the raw materials used are prepared according to the stoichiometric ratio. The raw materials, amounts, chemical formulas, pre-sintering / calcining temperatures and holding times of each compound in Examples 5-28 are shown in Table 1 below.

[0053] Table 1

[0054]

[0055]

[0056]

[0057] Embodiment 29

[0058] LED light source preparation: using commercial yellow phosphor YAG:Ce 3+ , Commercial red phosphor CaAlSiN3:Eu 2+ The blue-cyan light emitting fluorescent material obtained in Example 1 is combined, the ratio of the three is adjusted, and then packaged with a 400nm purple LED chip to obtain a white light LED light source device.

[0059] Comparative Example 1

[0060] LED light source preparation: using commercial blue phosphor BaMgAl 10 O 17 :Eu 2+ , red phosphor CaAlSiN3:Eu 2+ and yellow phosphor YAG:Ce 3+ The three are combined and the ratio is adjusted, and then packaged with a 400nm purple LED chip to obtain a white light LED light source device.

[0061] The photoelectric performance of LED light sources was tested using the Hangzhou Yuanfang Optoelectronics LED light color testing system (HASS2000).

[0062] The lumen efficiencies of Example 29 and Comparative Example 1 are 181 lm / W and 104 lm / W respectively. Figure 3 and Figure 4 ) It can be seen that the white light LED light source obtained in Example 29 has less harmful blue light (λ em =420-450nm), and can effectively fill the cyan "gap", and has a higher color rendering index and a lower correlated color temperature. This shows that the luminescent material obtained in Example 29 is conducive to improving the display index of the material and can obtain an ideal full spectrum.

[0063] The phase analysis test of the luminescent material in the embodiment was carried out using an X-ray diffractometer (DMAX 2500PC, Rigaku Corporation, Japan), and the excitation spectrum and emission spectrum of the luminescent material in the embodiment were tested using an FLS 980 (Edinburgh Instruments) fluorescence spectrometer.

[0064] Testing method for internal quantum yield, external quantum yield and absorption efficiency: Use FLS 980 (Edinburgh Instruments) fluorescence spectrometer equipped with a 450W xenon lamp coupled to an optical integrating sphere, and then use a standard halogen tungsten lamp to calibrate the optical response of the above instrument, and then test and calculate the internal quantum yield, external quantum yield and absorption efficiency of the material.

[0065] Thermal stability (200°C / 25°C) test method: Place the luminescent material on a heating platform (77-873K, THMS600, Linkam Scientific Instruments), control the sample holder temperature through a temperature control program, and use an FLS 980 (Edinburgh Instruments) fluorescence spectrometer to collect the emission spectra of the samples at different temperatures (25-200°C). The thermal stability of the material is analyzed and evaluated through the integrated intensity values ​​of the emission spectra at different temperatures.

[0066] from Figure 2 It can be seen that the Bi prepared in Example 1 3+ The activated fluorescent material has high luminescence brightness, and the emitted fluorescence wavelength is in the range of 400-600nm, with the strongest emission peak at ~470nm. Its excitation wavelength can well cover the purple region (395-420nm) and can be well matched with the purple LED chip. In addition, other test results of the present invention are shown in Table 2.

[0067] Table 2 Performance parameters of the embodiments

[0068]

[0069]

[0070] Finally, the following statement is made on the protection scope of the present invention: the above-listed embodiments are only exemplary descriptions of the present invention and are by no means limiting of the embodiments. Therefore, any changes in different forms and methods made by those skilled in the art based on the above description should be within the protection scope of the present invention.

Claims

1. A luminescent material emitting blue-cyan light, characterized in that: The chemical composition of the luminescent material is: A3B2Ge3O 12 :xBi 3+ ,in: A is one of Ca, Sr, Ba, Zn, Mg divalent metal ions or a combination thereof; B is one of the trivalent metal ions of La, Gd, Lu, Sc, Y, Al, Ga, and In, or a combination thereof; x is Bi 3+ The doping concentration is 0 <x≤0.20。 2. The luminescent material according to claim 1, characterized in that: The luminescent material can be excited by 330-420nm near-ultraviolet light / violet light to emit adjustable broadband blue-cyan light, and the emission range is: 420-580nm.

3. The luminescent material according to claim 1, characterized in that: The chemical composition of the luminescent material may be: Sr2MgLaScGe3O 12 :0.10Bi 3+ 、Sr2MgGdScGe3O 12 :0.10Bi 3+ 、Sr2MgYScGe3O 12 :0.10Bi 3+ 、Sr2MgLuScGe3O 12 :0.10Bi 3+ 、Sr2MgAlScGe3O 12 :0.10Bi 3+ 、Sr2MgGaScGe3O 12 :0.10Bi 3+ 、Sr2MgInScGe3O 12 :0.10Bi 3+ 、Sr2ZnLaScGe3O 12 :0.10Bi 3+ 、Sr2ZnGdScGe3O 12 :0.10Bi 3+ 、Sr2ZnYScGe3O 12 :0.10Bi 3+ 、Sr2ZnLuScGe3O 12 :0.10Bi 3+ 、Sr2ZnAlScGe3O 12 :0.10Bi 3+ 、Sr2ZnGaScGe3O 12 :0.10Bi 3+ 、Sr2ZnInScGe3O 12 :0.10Bi 3+ 、Ca2MgLaScGe3O 12 :0.10Bi 3+ 、Ca2MgGdScGe3O 12 :0.10Bi 3+ 、Ca2MgYScGe3O 12 :0.10Bi 3+ 、Ca2MgLuScGe3O 12 :0.10Bi 3+ 、Ca2MgAlScGe3O 12 :0.10Bi 3+ 、Ca2MgGaScGe3O 12 :0.10Bi 3+ 、Ca2MgInScGe3O 12 :0.10Bi 3+ 、Ca2ZnLaScGe3O 12 :0.10Bi 3+ 、Ca2ZnGdScGe3O 12 :0.10Bi 3+ 、Ca2ZnYScGe3O 12 :0.10Bi 3+ 、Ca2ZnLuScGe3O 12 :0.10Bi 3+ 、Ca2ZnAlScGe3O 12 :0.10Bi 3+ 、Ca2ZnGaScGe3O 12 :0.10Bi 3+ 、Ca2ZnInScGe3O 12 :0.10Bi 3+ 、Ba2MgLaScGe3O 12 :0.10Bi 3+ 、Ba2MgGdScGe3O 12 :0.10Bi 3+ 、Ba2MgYScGe3O 12 :0.10Bi 3+ 、Ba2MgLuScGe3O 12 :0.10Bi 3+ 、Ba2MgAlScGe3O 12 :0.10Bi 3+ 、Ba2MgGaScGe3O 12 :0.10Bi 3+ 、Ba2MgInScGe3O 12 :0.10Bi 3+ 、Ba2ZnLaScGe3O 12 :0.10Bi 3+ 、Ba2ZnGdScGe3O 12 :0.10Bi 3+ 、Ba2ZnYScGe3O 12 :0.10Bi 3+ 、Ba2ZnLuScGe3O 12 :0.10Bi 3+ 、Ba2ZnAlScGe3O 12 :0.10Bi 3+ 、Ba2ZnGaScGe3O 12 :0.10Bi 3+ 、Ba2ZnInScGe3O 12 :0.10Bi 3+ 。 4. The luminescent material according to claim 1 and claim 2, characterized in that: The method for preparing the luminescent material comprises the following steps: (1) According to the chemical formula of the material A3B2Ge3O 12 :xBi 3+ Weigh the compound raw materials and additives of each element in a stoichiometric ratio, add grinding media and grind thoroughly; (2) placing the obtained mixture into a corundum crucible, placing it in a box furnace for pre-sintering, cooling it naturally to room temperature after the pre-sintering is completed, and grinding the obtained pre-sintered product thoroughly, and then placing it in a tube furnace for calcining in an air atmosphere, and cooling it to room temperature with the furnace after the sintering is completed; (3) The sintered product obtained above is fully ground, cleaned, dried and sieved to obtain the target material; Optionally, the auxiliary agent described in step (1) may be selected from: NaCl, Na2O, LiCl, Li2CO3, H3BO3, Si3N4, Gd2O3, CaF2, SrF2, BaF2, MgF2, ZnF2, AlF3; Optionally, the grinding medium in step (1) may be: methanol, ethanol, ultrapure water; Optionally, the grinding time in step (1) can be selected as: 20-120 min; Optionally, the pre-firing temperature in step (2) may be 100-300° C., and the holding time may be 2-4 hours. Optionally, the calcination temperature in step (2) may be 1200-1400° C., and the holding time may be 2-24 hours. Optionally, the cleaning reagent described in step (3) can be selected from: acetic acid, ethanol, methanol, acetone, ultrapure water, the centrifugation time is: 3-5min, and the centrifugation speed is: 2000-5000 rpm; Optionally, the standard test sieve mesh number described in step (3) can be selected as: 30 mesh / 60 mesh / 120 mesh.

5. The luminescent material according to claim 1, characterized in that: The luminescent material can be used to realize a full-spectrum LED light source, and can be applied to the fields of healthy lighting, special place lighting, high-power lighting, etc.

Citation Information

Patent Citations

  • Bi &lt; 3 + &gt;-doped cyan fluorescent powder as well as preparation method and application thereof

    CN116120927A

  • Phosphor, light emitting device using phosphor, and display and lighting system using light emitting device

    US20070085466A1